2014
DOI: 10.1007/s00467-013-2748-5
|View full text |Cite
|
Sign up to set email alerts
|

Eculizumab therapy in a patient with dense-deposit disease associated with partial lipodystropy

Abstract: Our case emphasizes the efficacy of eculizumab in the management of crescentic DDD in a patient with a normal renal function, in a short follow-up period. Considering previously reported cases, it appears that eculizumab represents a promising new approach which may prevent progression to ESRD in a subset of patients with DDD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 13 publications
0
28
0
Order By: Relevance
“…Eculizumab is registered for use in paroxysmal nocturnal hematuria (11) and atypical hemolytic uremic syndrome (HUS) (12). Recent reports have described the use of eculizumab in DDD, with varying results (13)(14)(15)(16)(17)(18)(19)(20)(21).…”
Section: Introductionmentioning
confidence: 99%
“…Eculizumab is registered for use in paroxysmal nocturnal hematuria (11) and atypical hemolytic uremic syndrome (HUS) (12). Recent reports have described the use of eculizumab in DDD, with varying results (13)(14)(15)(16)(17)(18)(19)(20)(21).…”
Section: Introductionmentioning
confidence: 99%
“…A growing number of case reports have detailed the use of anti-complement C5 therapy, specifically eculizumab, as treatment for DDD both before and after transplantation (44,(47)(48)(49)(50).…”
Section: Treatment Today and Into The Futurementioning
confidence: 99%
“…Eight individual patients were reported, [73][74][75][109][110][111][112][113] showing success in seven patients. These optimistic results may be influenced by publication bias and contrast with the more modest effects obtained in an open-label proof-of-concept study in six patients.…”
Section: Inhibit Complement Activationmentioning
confidence: 99%
“…The phenotypic expression (DDD or C3 GN) does not seem to predict the response to treatment, 68,[73][74][75][109][110][111][112][113] although biomarker studies have suggested a greater terminal pathway activity in C3 GN compared with DDD. 115 In contrast, elevated soluble membrane attack complex was found to be a marker of response 68 in accordance with the mechanism of action of eculizumab on terminal pathway activation.…”
Section: Inhibit Complement Activationmentioning
confidence: 99%